Osteoimmunology: Major and Costimulatory Pathway Expression Associated with Chronic Inflammatory Induced Bone Loss - Tania N. Crotti; Anak A. S. S. K. Dharmapatni; Ekram Alias; David R. Haynes (Journal of Immunology Research)
The field of osteoimmunology has emerged in response to the range of evidences demonstrating the close interrelationship between the immune system and bone metabolism. This is pertinent to immune-mediated diseases, such as rheumatoid arthritis and periodontal disease, where there are chronic inflammation and local bone erosion. Periprosthetic osteolysis is another example of chronic inflammation with associated osteolysis. This may also involve immune mediation when occurring in a patient with rheumatoid arthritis (RA). Similarities in the regulation and mechanisms of bone loss are likely to be related to the inflammatory cytokines expressed in these diseases. This review highlights the role of immune-related factors influencing bone loss particularly in diseases of chronic inflammation where there is associated localized bone loss. The importance of the balance of the RANKL-RANK-OPG axis is discussed as well as the more recently appreciated role that receptors and adaptor proteins involved in the immunoreceptor tyrosine-based activation motif (ITAM) signaling pathway play. Although animal models are briefly discussed, the focus of this review is on the expression of ITAM associated molecules in relation to inflammation induced localized bone loss in RA, chronic periodontitis, and periprosthetic osteolysis, with an emphasis on the soluble and membrane bound factor osteoclast-associated receptor (OSCAR).